Penerapan Visual Dan Gestural Prompts Pada Siswa Tunarungu Untuk Mengurangi Perilaku Agresif - Priskila, Vania (Action Research Literate, 2025)
This study aims to explore the application of visual and gestural prompts to reduce aggressive behavior among deaf students at Special School (SLB) X in Jakarta. The research employed a qualitative approach with a single-case study design. The main subject was SF, a 14-year-old deaf student, with supporting information obtained from the accompanying teacher (Teacher M). Data were collected through observation, in-depth interviews, and documentation. Findings revealed that the teacher naturally applied visual and gestural prompting techniques during learning, including the use of sign language, body movements, and visual media to help students comprehend concepts and manage their emotions. These techniques effectively reduced SF’s aggressive behavior in school. The study highlights the importance of behavioral approaches in special education, particularly through behavior modification based on visual and gestural prompting.